Editorial: The Artificial Intelligence in Translational Medicine and Biomedical Research, How Future Can be Shaped?!! - Karzan Abdulmuhsin Mohammad (BioMed Target Journal)
The new era of translational medicine is facing a special and unique transition as the Artificial Intelligence (AI) and Machine Learning (ML) advance. The latest findings in many laboratories around the globes are promising and paved the way toward extraordinary innovative development in the field of medicine and medical research.